Tujuan Pemidanaan dalam Hukum Pidana Nasional dan Fiqh Jinayah - nafi' mubarok (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2015)
Abstract: Crime is a pattern of behavior that is detrimental to ‎society and causing victims, that will cause a social reaction. ‎One form of social reaction is penal policy, which is a ‎strategy to resolve crime by the use of criminal law. In penal ‎policy is necessary to formulate a background or reasons for ‎the use of the criminal law, or commonly known as the ‎formulation of the Purposes of Punishment, which has the ‎function to (1) create a synchronization both physically and ‎culturally; (2) control functions, provide a philosophical ‎foundation, the basis of rationality and motivation of ‎punishment; (3) determine the ultimate purpose of the ‎criminal law, and (4) implementation of the norms of ‎criminal law. This paper focuses on the study of